The Existence of Digital Platforms and the Challenges in Enforcement of Indonesian Competition Law - Rhido Jusmadi (Universitas Negeri Semarang, 2023)
This paper delves into the transformative impact of digital platforms on the enforcement of Indonesian competition law. The advent of these platforms has revolutionized the competition law landscape, with their multisided nature marking a conceptual departure from traditional economic platforms. This study underscores the challenges faced by enforcement agencies in applying the efficiency and consumer welfare approach to business competition law cases involving digital platforms. Recognizing these challenges, there is a growing awareness of the need for an alternative enforcement perspective, notably emphasizing the principle of fairness. By combining an exploration of the unique challenges posed by digital platforms with the imperative for a nuanced enforcement approach, this research contributes to a comprehensive understanding of the complexities surrounding Indonesian competition law in the evolving digital era.